Evaluating the gains and losses from government policies- consumer and producer surplus - Salayeva Quvonchoy Rustam qizi (Peerian Journals Publishing, 2024)
This article is devoted to how consumer and producer surplus can be used to study the welfare effects of a government policy—in other words, who gains and who loses from the policy, and by how much. We also use consumer and producer surplus to demonstrate the efficiency of a competitive market— why the equilibrium price and quantity in a competitive market maximizes the aggregate economic welfare of producers and consumers. The consumer surplus refers to the difference between what a consumer is willing to pay and what they paid for a product. The producer surplus is the difference between the market price and the lowest price a producer is willing to accept to produce a good.
Keywords: welfare effects; efficiency; producer surplus